2018
DOI: 10.1007/s00402-018-2879-z
|View full text |Cite
|
Sign up to set email alerts
|

Cementless total hip arthroplasty for severely dislocated hips previously treated with Schanz osteotomy of the proximal femur

Abstract: THA for hips previously treated with SO is technically demanding. If careful preoperative planning is performed, successful treatment can be achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 27 publications
0
12
0
1
Order By: Relevance
“…Concerning the second research question, two studies [1,21], both retrospective case series, did not detail the survivorship of the implants; 13 others did, including one that directly compared the outcomes in cemented versus cementless stems [11].…”
Section: Search Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Concerning the second research question, two studies [1,21], both retrospective case series, did not detail the survivorship of the implants; 13 others did, including one that directly compared the outcomes in cemented versus cementless stems [11].…”
Section: Search Resultsmentioning
confidence: 99%
“…Concerning the third research question, timing of hardware removal was described in five studies [1,5,8,23,27], three historically controlled and two case series. Two studies (Nagi et al [19] and Iwase et al [11]) reported difficulties with hardware removal without specifying its timing; the other nine studies included in our systematic review could not be used to answer the third research question because they were silent on the issue of timing or difficulties associated with hardware removal.…”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations